Cosmopolitan culture and counterculture among Chinese youth: face-to-face communities in the smartphone era - Flavel, TH (2022)
Young Chinese people have come of age in a communicative environment that is radically new, involving near-pervasive mobile broadband internet access and unprecedented exposure to global media. I employ a mix of ethnographic and computational methods to compare two groups of cosmopolitan Chinese youth – elite university students and subcultural bohemians – to explore the political implications of their cosmopolitan communications. The cosmopolitanism of Chinese youth, understood as both communicative diversity and globalized cultural engagement, is shaped in divergent ways by the influence of China’s orthodox Confucian and heterodox cultural traditions, with marked implications for patterns of online and offline communication. Constraints imposed by the university environment and Confucian social norms embed elite students in homogeneous networks that their extensive online communications do little to diversify. Exposure to the competing perspectives of global and domestic news and academic content generates both a normative relativism and a sophisticated grasp of practical political possibilities and constraints. This supports a hierarchical and pragmatic politics in which both national interests and those of their own social echelon, including progressive identity claims, are seen as being furthered by meritocratic authoritarianism. By contrast, bohemian proclivities for free-wheeling face-to-face interaction embed them in heterogeneous, cross-cutting networks, within which they synthesize discontents from diverse areas of Chinese society; combined with the influence of the heterodox tradition and the oppositional symbolic repertoires of global subcultures, this results in an egalitarian and reductively idealistic politics that supports opposition to the Party-State and its authoritarian system. The dominance of elite students’ orthodox cosmopolitanism suggests that the internet-mediated, globalized communications of Chinese youth constitute little immediate threat to the authoritarian system. However, the increasing scale and influence of bohemian heterodox cosmopolitanism and its idealistic politics, driven by factors beyond the control of Party-State, may ultimately undermine the manageability of Chinese youth.